2005
DOI: 10.1016/s0140-6736(05)67889-0
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of dementia: a Delphi consensus study

Abstract: We believe that the detailed estimates in this paper constitute the best currently available basis for policymaking, planning, and allocation of health and welfare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
3,164
7
203

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 4,662 publications
(3,409 citation statements)
references
References 23 publications
35
3,164
7
203
Order By: Relevance
“…Moreover, we have to underline that the comprehensive geriatric assessment we performed also considered objective determinants of the Only about 11% of our sample of depressed older adults were attending a DC. This seems to be a low rate of attendance, yet if we compare it with the rate of attendance of DCs (both regular and specific DCs) in all communitydwelling subjects with dementia (28%) (Georges et al 2008), we believe we have found results of a reasonable magnitude taking into account that: (i) dementia and depression have a similar prevalence in the communitydwelling older population (Ferri et al 2005;Unutzer 2007),…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, we have to underline that the comprehensive geriatric assessment we performed also considered objective determinants of the Only about 11% of our sample of depressed older adults were attending a DC. This seems to be a low rate of attendance, yet if we compare it with the rate of attendance of DCs (both regular and specific DCs) in all communitydwelling subjects with dementia (28%) (Georges et al 2008), we believe we have found results of a reasonable magnitude taking into account that: (i) dementia and depression have a similar prevalence in the communitydwelling older population (Ferri et al 2005;Unutzer 2007),…”
Section: Discussionmentioning
confidence: 85%
“…Finally, most studies investigating the effect of smoking on dementia were conducted with Western populations,13, 17 with relatively few studies conducted in Asia. As there are differences in prevalence18 and type distribution19 of dementia among Western and Asian populations, the effect of smoking on the risk of dementia might also differ between ethnic groups. Therefore, we aimed to investigate the effect of smoking habit change on the risk of developing dementia in this population‐based study using the Korean National Health Insurance System – National Health Screening Cohort (NHIS‐HealS).…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the World Health Organization estimated the number of persons with AD-related dementia at 35.6 million, which is expected to triple by 2050 to over 115 million [1]. The projected number of persons with AD in the USA by 2050 is 13.5 million, and the medical costs will exceed $20 trillion over the next 40 years [2,3]. The measurable socioeconomic annual costs of the disease on a global scale were estimated to exceed $600 billion in 2010 [1,4].…”
Section: Introductionmentioning
confidence: 99%